A companion to the ancient Near East - Snell, Daniel C. (Blackwell companions to the ancient world. Ancient history., 2005)
A Companion to the Ancient Near East offers students and general readers a comprehensive overview of Near Eastern civilization from the Bronze Age to the conquests of Alexander the Great. Written by leading experts, the book examines all the major civilizations of the region, including the Sumerians, Hittites, Babylonians, Assyrians, Israelites, and Persians. The Companion provides a survey of both the history of the Ancient Near East and the sources for studying the period. It places special emphasis on social and cultural history and also covers the legacy of the Ancient Near East in the med.